Determinants of critical infrastructure resources - Teresa Ostrowska; Tadeusz Krupa (Foundations of Management, 2017)
This article is devoted to the issue of how resources are interpreted in the form of technology reactors that, as a result of unexpected circumstances, turn into pyramidal or avalanche threat dynamics. Counteracting such catastrophic, terrorist, or war situations cannot begin in the face of mass casualties or significant material losses that will require reconstruction and the work of many generations. The decisive factor is the correct long-term operation and management of the economy. The starting point of this article is the concept of resource and structural-functional relationships of resources and all their possible interpretations consistent with the functionalities they play in the human environment, human aggregates, and whole nations. The aim is to draw the reader's attention to the importance (semiotics) of qualitative specifications and dynamically changing determinants contained in the material and structural-functional properties of the resources and their channel (information) communication.
Keywords: 650; technology reactor; resource; structural-functional properties of the resources; cluster resource model for threats; resource transformation process